2021
DOI: 10.1039/d1ra03455c
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable triazine-derived quaternary ammonium salts as antimicrobial agents

Abstract: The first examples of highly efficient antimicrobial triazine-derived bis imidazolium quaternary ammonium salts (TQAS) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…They found that the side chain length of 14 had the best antibacterial effect. 67 Relevant reports pointed out that imidazole derivatives are expected to be promising antibacterial materials with high activity against multidrug-resistant bacteria. 68 Other heterocyclic QASs, such as derivatives of piperidine and pyridine, also exhibit highly effective antibacterial and antimicrobial activities.…”
Section: Chemical Diversity Of Antibacterial Qassmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the side chain length of 14 had the best antibacterial effect. 67 Relevant reports pointed out that imidazole derivatives are expected to be promising antibacterial materials with high activity against multidrug-resistant bacteria. 68 Other heterocyclic QASs, such as derivatives of piperidine and pyridine, also exhibit highly effective antibacterial and antimicrobial activities.…”
Section: Chemical Diversity Of Antibacterial Qassmentioning
confidence: 99%
“…Morandini et al synthesized a triazine compound with a long alkyl group and then reacted it with methylimidazole to prepare triazine-derived quaternary ammonium salts (TQASs) with two units of positive charge. They found that the side chain length of 14 had the best antibacterial effect . Relevant reports pointed out that imidazole derivatives are expected to be promising antibacterial materials with high activity against multidrug-resistant bacteria .…”
Section: Chemical Diversity Of Antibacterial Qassmentioning
confidence: 99%
“…Likewise, molecular hybrids of s -triazine and imidazole (62) are also reported as quaternary ammonium salts as potent antibacterial agents. 71 Using the sustainable methodology, 2,4-dichloro-6-alkylamine- s -triazine was reacted with methyl imidazole to synthesize the targeted products in a very good yield of ∼90% in lesser time of 1.5 hours involving haloalkanes as the reactant. The chain length of the alkyl group ranged from C10–C18.…”
Section: Biological Activities Of S -Triazine-base...mentioning
confidence: 99%
“…Recently, antimicrobial peptides, 13,14 cationic compounds, 15-17 metal nanoparticles, 18,19 and polymer nanoparticles [20][21][22] have received considerable attention because of their broad-spectrum activities. They absorb on the membranes of bacterial cell and induce leakage of the cell contents.…”
Section: Introductionmentioning
confidence: 99%